Peeling Back the Layers of the Bleomycin Model of Lung Fibrosis: Lessons Learned, Factors to Consider, and Future Directions - Brazee, Patricia; Allen, Nancy; Knipe, Rachel; Redente, Elizabeth F.; Le Saux, Claude Jourdan (Seminars in Respiratory and Critical Care Medicine, 2025)
Bleomycin-induced lung injury remains the most widely used and well-characterized experimental model for studying pulmonary fibrosis, particularly idiopathic pulmonary fibrosis (IPF). This review provides a comprehensive analysis of the bleomycin model's utility, phases, variability, and translational relevance. Bleomycin administration in rodents induces acute epithelial injury followed by inflammation, fibroblast activation, extracellular matrix deposition, and eventual fibrosis. The model progresses through defined stages, acute inflammation (days 1–7), fibrogenesis (days 7–28), and in most cases, spontaneous resolution (days 42–63), making it suitable for understanding temporal aspects of fibrosis and repair, the cell populations involved, and the signaling mechanisms involved. Despite its advantages, the single-dose model lacks key features of human IPF, including persistent fibrosis, honeycomb cysts, and fibroblastic foci. Repetitive dosing and the use of aged mice have improved chronicity and recapitulation of progressive disease and observation of the expansion of aberrant epithelial cell populations in simple cyst structures. This review discusses route-specific effects, strain and sex susceptibilities, and the growing role of microbiome and genetic background in influencing fibrosis outcomes. It also highlights cellular responses across epithelial cell populations, fibroblasts, endothelial cells, and immune cell populations. Although limitations exist in this model—such as reversibility and incomplete modeling of human pathology—bleomycin remains invaluable for mechanistic studies and preclinical drug screening. Importantly, all FDA-approved antifibrotic drugs demonstrated efficacy in bleomycin models prior to clinical success. The review advocates for careful model selection, incorporation of persistent fibrosis models, and parallel use of human-relevant systems to enhance translational relevance in pulmonary fibrosis research.
Keywords: mouse model; pulmonary fibrosis; bleomycin